2020
DOI: 10.1371/journal.pone.0227609
|View full text |Cite
|
Sign up to set email alerts
|

A highway crash risk assessment method based on traffic safety state division

Abstract: In order to quantitatively analyze the influence of different traffic conditions on highway crash risk, a method of crash risk assessment based on traffic safety state division is proposed in this paper. Firstly, the highway crash data and corresponding traffic data of upstream and downstream are extracted and processed by using the matched case-control method to exclude the influence of other factors on the model. Secondly, considering the weight of traffic volume, speed and occupancy, a multi-parameter fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In recent years, the concept of active safety has gradually entered the vision of researchers. More and more studies [8][9][10] have found that trafc fow state has a strong correlation with the road trafc crash occurrence. For example, Lee et al used the trafc fow data within 5 minutes before the crash to study the infuence of trafc fow dynamic characteristics on the collision pattern of the crash [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the concept of active safety has gradually entered the vision of researchers. More and more studies [8][9][10] have found that trafc fow state has a strong correlation with the road trafc crash occurrence. For example, Lee et al used the trafc fow data within 5 minutes before the crash to study the infuence of trafc fow dynamic characteristics on the collision pattern of the crash [11].…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of traffic accident risk management depends on the achievement of each supporting performance system indicator (da Costa et al, 2016). Road safety management and control has the main task of assessing the risk of traffic accidents based on case studies in order to improve the control of the risk of high traffic accidents in traffic (Sun et al, 2020).…”
Section: Go Downmentioning
confidence: 99%
“…However, if significant fatal-collision causative factors are identified, those factors could also be considered in the likelihood function. Therefore, evaluating the impact of other causative factors such as weather, roadway geometry, and traffic characteristics in classifying sites as R [34][35][36][37] and other likelihood functions that consider those factors will be the subjects of future study. The authors also plan to further evaluate the performance of the proposed method along rural highways or urban area where the characteristics of fatal collisions can differ from those of this study [38].…”
Section: Plos Onementioning
confidence: 99%